The Peruvian university professor and the virtuality in the health emergency - Vargas-Salazar, Ivonne Yanete; Motta-Flores, Madalyne; Cortez-Cortez de Uceda, Gaby Rosario (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
During the current global health crisis, governments have dictated emergency measures; as a result, Peruvian universities interrupted academic work and began remote teaching. The changes from an in- person to non-face-to-face teaching process and adaptation of teachers to virtual teaching are analyzed. It is a mixed investigation, performing regressions and characterizing each component. Connectivity gaps, knowledge in digital tools, pedagogical and technological approach are identified that affect efficiency and teaching productivity of the non-face-to-face teaching process. The university community needs to develop and reinforce new techno-pedagogical capacities towards hybrid education in a new normal scenario.